Identifikasi Kebutuhan Ruang Terbuka Hijau Publik Dengan Pemanfaatan Penginderaan Jauh DanSistem Informasi Geografis Di Wilayah Perkotaan Boyolali Tahun 2015 - Rahmadi, Dimas Santoso, Drs. H. Yuli Priyana, M.Si, Agus Anggoro Sigit, S.Si, M.Sc (2015)
Research on the identification of green open space public needs is done in the urban Boyolali. The purpose of this study for (1)the identification of points of public green open space which would then be used as a priority area of public green open space sustainable and (2) analyzing the need for public green open space in cities Boyolali vast green open space that is available to the broad public urban area Boyolali and needs of the population The method used in this research is to use the survey method.. Determination ofthe field surveyusingstratified samplingmethodbasedonland units.Survey method aims to illustrate the need for open green space in the urban area Boyolali. Taking samples for its own research using random sampling method, which means sampling technique is done by grounding think that all members of the population have the same chance as a member of the sample selected.Analysis to obtain results that are used in this study is that spatial analysis using Geographic Information System software that serves to identify the existing green open space public Results from this study obtained broad green open space public urban area Boyolali amounted to 477.88 hectare, or approximately 11% of the total area is 4248.85 hectare arban Boyolali.So the need for public green open space based on the vast territory still less 9%, which for the minimum area of green open space public is 20%.The Needs of green open space public urban area Boyolali by population in 2014 was 2.38 hectares, or approximately 0.056% of the total area urban Boyoali.for projected population in the year 2034 needs public green open space is 2.7 hectares, or approximately 0.063% of the total area